2018
DOI: 10.1111/1467-6427.12232
|View full text |Cite
|
Sign up to set email alerts
|

Family factors associated with self‐harm in adults: a systematic review

Abstract: The aim of this study was to systematically review the literature pertaining to family dynamics in the adult self‐harming population. PsycINFO, Medline, Cumulative Index to Nursing and Allied Health Literature (CINAHL) and Applied Social Sciences Index and Abstracts (ASSIA) were searched for studies containing two keywords, one relating to self‐harm and the second relating to a family relationship. The final search was run on 4 August 2017. The electronic search yielded a total of 2,623 studies; 119 texts were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 44 publications
2
6
0
Order By: Relevance
“…Looking specifically at self-harm outcomes, our findings agree with results from small, cross-sectional studies with university student samples, showing that those who engage in self-harm report a poorer quality of attachment to parents compared to those who do not (Buckmaster, McNulty, & Guerin, 2019). The shared feature of emotional dysregulation found with both insecure attachment and self-harm (Gratz & Roemer, 2008) offers a possible explanation: when faced with stress, individuals with emotion dysregulation may be less able to tolerate difficult emotions, and more likely to internalise distress, subsequently releasing it in the form of self-injuring behaviour (Ross & Heath, 2002).…”
Section: Discussionsupporting
confidence: 85%
“…Looking specifically at self-harm outcomes, our findings agree with results from small, cross-sectional studies with university student samples, showing that those who engage in self-harm report a poorer quality of attachment to parents compared to those who do not (Buckmaster, McNulty, & Guerin, 2019). The shared feature of emotional dysregulation found with both insecure attachment and self-harm (Gratz & Roemer, 2008) offers a possible explanation: when faced with stress, individuals with emotion dysregulation may be less able to tolerate difficult emotions, and more likely to internalise distress, subsequently releasing it in the form of self-injuring behaviour (Ross & Heath, 2002).…”
Section: Discussionsupporting
confidence: 85%
“…A semi-structured interview format was used. The interview scheduled (see Table 2) was derived from theoretical underpinnings of the subject areas and from topics identified by a recent systematic review of the literature (Buckmaster et al, 2019). Interviews were conducted by the first author and were audio recorded and later transcribed verbatim by the third author.…”
Section: Methodsmentioning
confidence: 99%
“…However, research in the area of family factors associated with self-harm in adults is in the preliminary stage. A recent systematic review identified twenty-seven studies which examined the phenomenon, twenty-three of which were cross-sectional studies and fifteen of which were conducted with a sample of university students (Buckmaster et al, 2019). The review indicated that insecure attachment to parents and romantic partners is associated with self-harm.…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Less empirical research exists in the field of adult self-harm and family relationships. However, findings from a systematic review of family relationships for adults who self-harm (Buckmaster et al 2019) identified 27 studies which explored this phenomenon. This review indicated that insecure attachment to parents and romantic partners is associated with self-harm.…”
mentioning
confidence: 99%